The Effect of Quercetin on Plasma Interleukin-5, Blood Eosinophil Absolute, %FEV1, and Clinical Improvement of Asthma Alergy Patient - Hesti Nila Mayasari; Suradi Suradi; Ana Rima Setijadi (Jurnal Respirologi Indonesia, 2020)
Backgrounds: Asthma is a chronic airway inflammation which is a manifestation of complex interactions between cells and moleculer mediators. The aims asthma management is to reach asthma in controlled state. Providing an additional therapy in these circumstances is necessary to control asthma. Quercetin as an adjunctive therapy in asthma therapy may improve clinical symptoms and lung function. Methods: Experimental clinical trials of pretest of and postest design were conducted on 34 patient’s asthma at Dr. Moewardi Hospital Surakarta in 6 October–10 December 2018. Subject of treatment group (n= 17) was given quercetin 500 mg per day within 28 days, the control group (n=17) received only standar therapy asthma. Decreased airway inflammation was assessed based on the percentage of blood eosinophil and IL-5. Clinical improvement was assessed by ACT score while lung function used FEV1. Results: Quercetin decreased the inflammatory airways in patients with asthma evidenced by significant decrease in plasma IL-5 of treatment groups but no significant differences between treatment and control group, the mean decrease of blood eosinophil in the treatment group was significant. Querectin improved lung function with decrease FEV1 of treatment groups but no significant differences between treatment and control group and there was a clinical improvement with significant ACT score enhancement in the treatment group. Conclusion: The administration of quercetin significantly reduced inflammation based on decreased levels of eosinophils. There are improvement of lung function and clinical symptoms after quercetin. (J Respir Indo. 2020; 40(1): 16-23)